Germline BRCA1 Mutation Detected in a Multiple Endocrine Neoplasia Type 2 Case With RET Codon 634 Mutation - Sarkadi, Balázs; Baghy, Kornélia; Sápi, Zoltán; Nyirő, Gábor; Likó, István; Patócs, Attila (Frontiers in Genetics, 2019)
Introduction: Coincidence of more than one pathogenic mutation in high and/or moderate-risk-associated cancer genes have been rarely reported, and the implication for disease progression has been debated. We present a case harboring two autosomal dominant inherited mutations potentially aggravating the phenotype. Case report: A 16-year-old female was referred to the Endocrine Unit due to hair loss. Two heterogeneous masses in the thyroid gland were confirmed as medullary thyroid carcinoma. Genetic testing revealed a pathogenic RET mutation associated with Multiple Endocrine Neoplasia type 2 (MEN2). Genetic screening identified the same mutation in the proband’s clinically negative brother, and in his two sons. The proband’s mother and maternal aunt died of breast cancer. No samples were available from the deceased. The proband underwent further genetic counseling and BRCA1/2 testing. A novel, frameshift mutation (BRCA1 Ile90Serfs, NC_000017.10:g.41256905_41256917) was identified in the proband but it was absent in the brother and father, indicative of maternal inheritance. Breast or ovarian cancer was not detected in our case. Conclusion: Coincidence of two monogenic autosomal dominant tumor syndromes is extremely rare, representing significant therapeutic and cancer surveillance challenges. Due to the wider use of next generation sequencing in clinical practice similar situations may occur more frequently.